PENINGKATAN HASIL BELAJAR KIMIA MATERI SENYAWA HIDROKARBON SISWA SMAN 1 KALIWUNGU DENGAN METODE â€TUBA ASYIKâ€ - Wiqoyati, Siti Nur (Universitas Negeri Semarang, 2013)
The background of this study was the reality that the understanding of students in classÂ X of SMAN 1 Kaliwungu about Hydrocarbon compounds is still very low. Learning method thatÂ has been done was the discussion of information and exercises. Studentsâ€™ attention was initiallyÂ 100%, but weakened after a such period and just when students did exercises, they seemed toÂ lose of desire to learn. The change of teaching methods used was attempted by using the method Â of Tuba Asyik, the method of peer tutor combined with the fun games. This action researchÂ consisted of two cycles, each of which had a step of plan-action-observation-reflection. TheÂ analysis used was a qualitative and quantitative analysis, while the validation of the data usedÂ was triangulation. The percentage of attendance of students in Cycle I and Cycle II was 100%.Â The number of students who are enthusiastic about taking on the learning process was 65% PreCycle,Â CycleÂ I was 90%, in Cycle II was 92.5%. Classical Thoroughness of Learning in Cycle I was 78% and that in Cycle II was 85%. These figures showed that Tuba Asyik method was anÂ appropriate and effective mthod to improve student learning outcomes in hydrocarbon compoundÂ topic.Keywords: TUBA Asyik MethodÂ